INDUKSI MUTASI PADA BUNGA MATAHARI (Helianthus annus L) MELALUI IRADIASI SINAR GAMMA - Saragih, Siti Hartati Yusida (Program Studi Agroteknologi, Fakultas Sains dan Teknologi, Universitas Labuhanbatu, 2018)
Sunflower (Helianthus annus L.) is one of the ornamental plant which is economically. It is potential because of oil contains and has the beautiful flower. Induced mutation is important to get genetic diversity of Sunflower. Mutations are genetic changes in either a single cell or a number of genes or chromosomal changes that can cause somaclonal variations. This research was aimed to find the LD20 and LD50 and to identify genetic diversity of Sunflower with the dosage 0, 150, 200, 250 and 300 Gy. The results showed that the higher LD20 and LD50 was at 158.338 gy and 260.339 gy. The gamma ray iradiation was induce variation and affected significantly toward quantitative character of plant height. Key words: diversity, induced mutation, iradiation, LD20, LD50